2020
DOI: 10.3390/gels6030022
|View full text |Cite
|
Sign up to set email alerts
|

Volume Phase Transition in Gels: Its Discovery and Development

Abstract: The history of volume phase transition of responsive gels from its theoretical prediction to experimental discovery was described and the major role of mixing Gibbs energy function in theoretical models was stressed. For detailed analysis and fine tuning of the volume phase transition, the generalized Flory–Huggins model with concentration and temperature dependent interaction function coupled with Maxwell construction as a tool is very suitable. Application of expansive stresses can uncover the potential of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 78 publications
0
21
0
Order By: Relevance
“…This volume change may occur gradually (continuous), or drastically (discontinuous) as a first-order volume phase transition. The discontinuous volume phase transition in gels from swollen to collapsed states, similar to the coil-to-globule transition of a single polymer chain, was first predicted in 1968 by Dusek and Paterson [ 7 , 12 ]. They showed that, under certain conditions, the chemical potential of the solvent in a gel passes through two extremes when plotted against the polymer volume fraction (Equation (1a,b)).…”
Section: Swelling-deswelling Transition Of Stimuli Responsive Hydrogelsmentioning
confidence: 89%
“…This volume change may occur gradually (continuous), or drastically (discontinuous) as a first-order volume phase transition. The discontinuous volume phase transition in gels from swollen to collapsed states, similar to the coil-to-globule transition of a single polymer chain, was first predicted in 1968 by Dusek and Paterson [ 7 , 12 ]. They showed that, under certain conditions, the chemical potential of the solvent in a gel passes through two extremes when plotted against the polymer volume fraction (Equation (1a,b)).…”
Section: Swelling-deswelling Transition Of Stimuli Responsive Hydrogelsmentioning
confidence: 89%
“…Polyelectrolyte gels can show a discontinuous volume phase transition (DVPT) stimulated by, e.g., pH, temperature, or solvent composition and exhibit high swelling ratios due to an additional ionic free energy contribution for good solvent conditions at low salt concentrations. Polyelectrolyte tendomers (“tendolytes”) connected to a gel may show a similar behavior, but the nonlinear deformation behavior of tendomers alone will not cause a DVPT. Since the elastic free energy in the nonlinear regime differs qualitatively from ideal rubber elasticity, the corresponding changes for the free energy of the tendolyte gel may shift, enhance or even suppress a DVPT.…”
Section: Network Preparation For the Nonlinear Regimementioning
confidence: 99%
“…Of relevance to iTLS efforts, most hydrogel preparations can be injectable or transplantable depending on the timing and chemistries of the crosslinking steps, and can be formulated in large injection/implantation volumes or in micro or even nanoscale particle preparations (104). Because of their large capacity to hold aqueous solution, many hydrogel preparation methodologies are widely compatible with cell culture conditions so long as the chemistries required for crosslinking do not stray from physiologic pH, temperature, salinity, and other cell culture ranges (105)(106)(107). For this reason, crosslinking chemistries that utilize mild temperature or pH changes such as warming from 4°C to 37°C or changing from a slightly acidic solution to slightly basic are ideal for injectable preparations, as such hydrogels would crosslink after injection into living recipients (105,107).…”
Section: Hydrogelsmentioning
confidence: 99%